Guest editorial: INITIATING THE DEBATE: PERSPECTIVES ON TEACHING, LEARNING AND ASSESSMENT IN OPEN DISTANCE LEARNING CONTEXTS: INTRODUCTION TO THE SPECIAL EDITION - Prinsloo, Paul; Coetzee, Melinde (South African Journal of Higher Education, 2016)
This special issue of the South African Journal of Higher Education (SAJHE) dedicated to ODL presents articles from a range of disciplinary and institutional contexts that provide glimpses into the challenges, opportunities and issues relating to ODL praxis and research. Established in 1873, Unisa is not only the oldest distance education institution in the world, but is furthermore the largest distance education institution on the African continent and one of the mega universities in the world. In this special issue of the South African Journal of Higher Education (SAJHE) dedicated to ODL, it is therefore natural that a number of articles reflect on teaching, learning and assessment in the specific context of Unisa. This issue is honoured to also have contributions from a range of other Southern African and diverse international distance education contexts such as the University of Lesotho and SUNY Empire State College. Contributors to this special issue have vast experience in distance education ranging from experiences in Southern Africa, the Middle East, Russia, Europe and the United States of America.